(untitled) (Perner’s Contacts, 2014)
The article aims to investigate an impact of new STAR procedures intended to be implemented on the Kunovice airport (LKKU) compared with current state. The new Standard instrument Arrivals (STARs) and Departures (SIDs), which were designed according to the Performance Based Navigation (PBN) concept, are expected to bring benefits such as increased airspace capacity, flexibility or ATC controller workload decrease. The new procedures design is presented in first part of the article. In the second part, the article introduces the simulation tool Visual Simmod used for simulation experiment. The simulations on the models of new and current design on the several traffic samples are performed and the results are analyzed.